Approximation Properties of p, q-Szász-Mirakjan-Durrmeyer Operators. (11th March 2021) - Lin, Zhi-Peng; Cheng, Wen-Tao; Xu, Xiao-Wei
Abstract : In this article, we introduce a new Durrmeyer-type generalization of p, q -Szász-Mirakjan operators using the p, q -gamma function of the second kind. The moments and central moments are obtained. Then, the Voronovskaja-type asymptotic formula is investigated and point-wise estimates of these operators are studied. Also, some local approximation properties of these operators are investigated by means of modulus of continuity and Peetre K -functional. Finally, the rate of convergence and weighted approximation of these operators are presented.